2022
DOI: 10.3389/fpsyg.2022.873078
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Various Role Models on Children’s Pro-environmental Behaviours

Abstract: Although most schoolchildren can dispose of their own litter, they are typically not sensitive to environmental issues in the school’s public areas. How do we improve children’s sensitivity to public environments and cultivate pro-environmental behaviours? Based on Bandura’s social learning theory, this study explored the effects of various role models (teachers and peers) on the pro-environmental behaviours of children aged 7–13. A field study was conducted in which examples of postprandial garbage disposal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 100 publications
(97 reference statements)
0
0
0
Order By: Relevance
“…The results from the qualitative data are in line with past research describing the relevance of teachers as role models for their students (Lazarowitz and Naim 2013;Liang et al 2022), showing their potential influence in shaping children's pro-environmental behaviors. In addition, with specific regard to sustainable education, teachers can create a potential spillover effect toward parents (Duvall and Zint 2007;Lawson et al 2018); evidence shows that children can promote the acquisition of pro-environmental knowledge, attitudes, and beliefs with their close relatives.…”
Section: Discussionsupporting
confidence: 85%
“…The results from the qualitative data are in line with past research describing the relevance of teachers as role models for their students (Lazarowitz and Naim 2013;Liang et al 2022), showing their potential influence in shaping children's pro-environmental behaviors. In addition, with specific regard to sustainable education, teachers can create a potential spillover effect toward parents (Duvall and Zint 2007;Lawson et al 2018); evidence shows that children can promote the acquisition of pro-environmental knowledge, attitudes, and beliefs with their close relatives.…”
Section: Discussionsupporting
confidence: 85%
“…A relevant study on students aged between nine and thirteen years in Madrid led to the conclusion that peers did indeed affect environmental behaviors, with girls being more affected than boys [16]. However, a more recent study on students in the ages between 7-13 in China concluded that peers did not exert a substantial influence, at least for this age group, while peers' negative behavior patterns in relation to the environment did not affect children's environmental behavior [26].…”
Section: Factors Affecting the Formation Of Environmental Attitudesmentioning
confidence: 99%
“…Authoritative parents tend to encourage children to be happy, creative, and cooperative, displaying a combination of affective responses and attentiveness to their children's needs, especially considering their developmental and social dimensions. Conversely, parents with authoritarian attitudes are less warm, responsive, and consistent, often resorting to more punishment (Liang et al, 2022;Liu & Hoa Chung, 2022).…”
Section: Introductionmentioning
confidence: 99%